EFEKTIVITAS PROGRAM ALOKASI DANA DESA (ADD) DALAM PEMBERDAYAAN MASYARAKAT DI DESA LIANG ULU KECAMATAN KOTA BANGUN KABUPATEN KUTAI KARTANEGARA - Jamiah Jamiah (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
In accordance with the guidelines for implementing village fund allocation (ADD) that one of the allocations for Village Fund Allocation is for village development costs, but the problem now is that development should not only be oriented towards physical development, but also need human resource development through community empowerment .This type of research used in this research is descriptive qualitative. Data collection techniques using in-depth interviews, documentation and observation. Based on the background that has been described, the authors propose a problem that is the center of attention in the research as follows: 1). How is the effectiveness of the village fund allocation program (ADD) in community empowerment in Liang Ulu Village, Kota Bangun District, Kutai Kartanegara Regency. 2). What are the supporting and inhibiting factors in community empowerment in Liang Ulu Village, Kota Bangun District, Kutai Kartanegara Regency. While the objectives of this study can be formulated as follows: 1) To find out and describe the effectiveness of the village fund allocation program (ADD) in Community Empowerment in Liang Ulu Village, Kota Bangun District, Kutai Kartanegara Regency. 2) To determine the supporting and inhibiting factors in community empowerment in Liang Ulu Village, Kota Bangun District, Kutai Kartanegara Regency.The results show that the effectiveness of the Village Fund Allocation program in Community Empowerment in Liang Ulu Village, Kota Bangun District, Kutai Kartanegara Regency is as follows: Achieving the effectiveness of the Village Fund Allocation Program (ADD) in community empowerment in Liang Ulu Village, Kota Bangun District, Kutai Kartanegara Regency in terms of achievement of goals has been running quite effectively. Because in its implementation the village government has made programs and policies for community empowerment in Liang Ulu Village, be it from business assistance activities such as making wheat crackers, or assistance from the poor, assistance in making fish trap ponds through BUMDes borrowing siampan, infrastructure development such as ironwood bridges connecting roads in riverbank areas with major roads that involve the village community, and training provided by the village government to its residents, such as sewing training, workshop training, fishery cultivation training and others.